Mechanism of unfolding of human prion protein - Singh, R. K.; Chamachi, N. G.; Chakrabarty, S.; Mukherjee, A. (Journal of Physical Chemistry B, 2017)
Misfolding and aggregation of prion proteins are associated with several neurodegenerative diseases. Therefore, understanding the mechanism of the misfolding process is of enormous interest in the scientific community. It has been speculated and widely discussed that the native cellular prion protein (PrPC) form needs to undergo substantial unfolding to a more stable PrPC* state, which may further oligomerize into the toxic scrapie (PrPSc) form. Here, we have studied the mechanism of the unfolding of the human prion protein (huPrP) using a set of extensive well-tempered metadynamics simulations. Through multiple microsecond-long metadynamics simulations, we find several possible unfolding pathways. We show that each pathway leads to an unfolded state of lower free energy than the native state. Thus, our study may point to the signature of a PrPC*. form that corresponds to a global minimum on the conformational free-energy landscape. Moreover, we find that these global minima states do not involve an increased beta-sheet content, as was assumed to be a signature of PrPSc formation in previous simulation studies. We have further analyzed the origin of metastability of the PrPC form through free energy surfaces of the chopped helical segments to show that the helices, particularly H2 and H3 of the prion protein, have the tendency to form either a random coil or a beta-structure. Therefore, the secondary structural elements of the prion protein are only weakly stabilized by tertiary contacts and solvation forces so that relatively weak perturbations induced by temperature, pressure, pH, and so forth can lead to substantial unfolding with characteristics of intrinsically disordered proteins.

Heterogeneous nucleation in citrate synthesis of AgNPs: effect of mixing and solvation dynamics - Deshpande, J. B.; Chakrabarty, S.; Kulkarni, A. A. (Chemical Engineering Journal, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">The heterogeneity issues in silver nanoparticle nucleation (Lee-Meisel route) have been investigated. The final polydispersity and sphericity of the nanoparticles in the Lee-Meisel scheme are shown to depend upon the early time dynamics of silver-citrate complexation. The formation of macromolecular intermediary complexes in the early stages of the reaction is visualized based on online DLS data, TEM analysis, and the mass balances of silver and citrate ions. The reversible complexation between citrate ions and silver citrate is shown to be the limiting step that governs the directional growth of the nanoparticles. The dynamics of the complexation of citrate are seen to form a very rapid step and intense mixing was required for the complexation to happen uniformly across the reaction. This specific observation is also confirmed from the MD simulations. Thus, to get particles of high sphericity, irrespective of the reaction concentration, temperature, or reactor geometry, the mixing time should be <4 s and <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Da<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> ~ 0.1. Optimal mixing conditions for isotropic growth are suggested based on the reaction kinetics and are also demonstrated with experimental evidence.